EFEKTIVITAS KITOSAN MIKROKRISTALIN SEBAGAI ALTERNATIF ANTIBAKTERI ALAMI DALAM MOUTHWASH - Bustami Ibrahim; Pipih Suptijah; Ahmad Zahid (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2012)
Microcrystalline chitosan is a chitosan that has been modified by minimizing its particle size. Chitosan posses antibacterial property. The use of microcrystalline chitosan as an antibacterial in the mouthwash has not been revealed yet. This study was done to compare the degree effectiveness of mouthwash that contain microcrystalline chitosan as an antibacterial and commercial mouthwash. The parameters measured in this study were proximate analysis, yield, deacetylation (Fourier Transform Infrared), particle size (Scanning Electron Microscopy), and total plate count. Microcrystalline chitosan contained moisture, ash, nitrogen and yield were 3.92% dry weight basis (db); 4% db, 1.4% db; and 50% respectively. Detection results of FTIR and SEM showed the size of microcrystalline chitosan was 0.6-6μm and degree of deacetylation was 88.66%. Mouthwash that contained 0.5%, 1% and 1.5% microcrystalline chitosan could reduce TPC bacteria up to 97.57%, 99.05% and 99.46% respectively, while commercial mouthwash reduced TPC bacteria up to 89.70%.Keywords: antibacterial, microcrystalline chitosan, mouthwash.